2005
DOI: 10.1177/002214650504600401
|View full text |Cite
|
Sign up to set email alerts
|

Geneticization of Deviant Behavior and Consequences for Stigma: The Case of Mental Illness

Abstract: One likely consequence of the genetics revolution is an increased tendency to understand human behavior in genetic terms. How might this "geneticization" affect stigma? Attribution theory predicts a reduction in stigma via reduced blame, anger, and punishment and increased sympathy and help. According to "genetic essentialist" thinking, genes are the basis of human identity and strongly deterministic of behavior. If such ideas are commonly accepted, geneticization should exacerbate stigma by increasing percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
382
6
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(414 citation statements)
references
References 35 publications
14
382
6
8
Order By: Relevance
“…13,30,31 Conversely empirical evidence suggests a genetic model for mental illness may increase the perceived seriousness of these disorders and increase stigma. 15,30,31 These findings are further supported by a study that found endorsement of genetic explanations decreased the likelihood of social acceptance of people with schizophrenia and major depression. 32 This study supports the evidence that knowledge of genetic susceptibility could carry potential for both health promotion and harm through genetic validation versus genetic discrimination, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…13,30,31 Conversely empirical evidence suggests a genetic model for mental illness may increase the perceived seriousness of these disorders and increase stigma. 15,30,31 These findings are further supported by a study that found endorsement of genetic explanations decreased the likelihood of social acceptance of people with schizophrenia and major depression. 32 This study supports the evidence that knowledge of genetic susceptibility could carry potential for both health promotion and harm through genetic validation versus genetic discrimination, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Attribution theory would predict that genetic causal attributions would decrease smoker-related stigma because the shift of control for the behavior is reframed as biological. However, research by Phelan (2005) on mental illness stigma suggests that genetic attributions not only fail to reduce stigmatizing beliefs but actually contribute to increases in some stigma-relevant domains. She argues that because genetic characteristics are seen as irrevocable, genetic essentialist thinking leads to greater stigmatization when applied to negative valued qualities because it contributes to perceptions that the person is fundamentally different from others, that the problem is persistent and serious, and that the problem is likely to occur in other family members.…”
Section: Attribution Theory and Stigmamentioning
confidence: 99%
“…Attribution theory suggests that "low causal responsibility for a stigmatized characteristic […] is associated with less blame and more positive emotions" (Phelan, 2005, p. 309). In other words, the assignation of blame for an outcome (for example, becoming or remaining addicted) will diminish if the behaviour is attributed to a characteristic over which an individual is considered to have limited control (for example, ones genetically determined constitution) (Phelan, 2005). However, as Phelan (2005) herself has demonstrated, a biological conception of mental illness may have multiple moral effects, including stigmatisation, particularly if the behaviour is seen as untreatable and the affected person is seen as likely to cause harm (Phelan and Link, 2012).…”
Section: Introductionmentioning
confidence: 99%